2019
DOI: 10.1101/786509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cover crops improve early season natural enemy recruitment and pest management in cotton production

Abstract: A shift to more ecologically based farming practices would improve the sustainability and economic stability of agricultural systems. Habitat management in and around agricultural fields can provide stable environments that aid in the proliferation of natural enemy communities that moderate pest populations and injury. Winter cover crops offer a potentially cost-effective approach to improving habitat that supports natural enemy communities early in the growing season. We investigated the effects of winter cov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…However, careful attention must be paid to selecting ground cover plants so they do not compete with the main tree for nutrients, water, and space so that the main plant growth remains optimal. A journal article in [6] states that the use of cover crops from wheat and clover on cotton plants revealed that cover crops significantly reduced thrips attacks. Also, chinch infestation decreases in plots prepared with wheat cover compared to cotton which lacks this additional habitat.…”
Section: Fig 3: Growth Of Chili Plants Intercropped With Corn (Using Plastic Mulch)mentioning
confidence: 99%
“…However, careful attention must be paid to selecting ground cover plants so they do not compete with the main tree for nutrients, water, and space so that the main plant growth remains optimal. A journal article in [6] states that the use of cover crops from wheat and clover on cotton plants revealed that cover crops significantly reduced thrips attacks. Also, chinch infestation decreases in plots prepared with wheat cover compared to cotton which lacks this additional habitat.…”
Section: Fig 3: Growth Of Chili Plants Intercropped With Corn (Using Plastic Mulch)mentioning
confidence: 99%
“…Conservation agriculture can improve pest management, particularly of arthropods, by fostering natural‐enemy populations (Tooker et al, 2020). Winter cover crops, for example, can harbor predator populations by providing living habitats and resources for predators outside the growing season of the cash crop (Bowers et al, 2020). Once killed, cover‐crop residues remain on the soil surface during the growing season and increase habitat for predators and alternative prey (e.g., arthropod decomposers) (Carmona & Landis, 1999).…”
Section: Introductionmentioning
confidence: 99%